2018
DOI: 10.1002/vnl.21632
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of fusion behavior of the nanocomposites based on poly(vinyl chloride)/poly(epichlorohydrin‐co‐ethylene oxide)/organoclay

Abstract: In this work, poly(vinyl chloride)/poly(epichlorohydrinco-ethylene oxide) (PVC/ECO)/organoclay nanocomposites were prepared via melt processing and their fusion behaviors were comprehensively investigated. In this way, response surface methodology was employed to study the main and interactive effects of three parameters (Cloisite 30B content, ECO content, and rotor speed) on fusion of the PVC matrix. The results showed that ECO rubber has a negative influence on the fusion process, while optimal levels of oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In our previous work, we used Poly(epichlorohydrin-co-ethylene oxide) (ECO) as an electrostatically dissipative compound to see its effect on fusion behavior of (PVC/ECO)/organoclay nanocomposites. 18 The results of our study, based on response surface method (RSM) showed that low levels of the ECO content, and low or medium levels of OMMT and rotor speed are the optimum conditions for lower fusion time (FT) and higher fusion factor (FF). In continuation of our previous work, herein, we are going to investigate the effect of ECO, OMMT, and rotor speed parameters on thermal stability of (PVC/ ECO)/OMMT nanocomposite.…”
Section: Introductionmentioning
confidence: 84%
“…In our previous work, we used Poly(epichlorohydrin-co-ethylene oxide) (ECO) as an electrostatically dissipative compound to see its effect on fusion behavior of (PVC/ECO)/organoclay nanocomposites. 18 The results of our study, based on response surface method (RSM) showed that low levels of the ECO content, and low or medium levels of OMMT and rotor speed are the optimum conditions for lower fusion time (FT) and higher fusion factor (FF). In continuation of our previous work, herein, we are going to investigate the effect of ECO, OMMT, and rotor speed parameters on thermal stability of (PVC/ ECO)/OMMT nanocomposite.…”
Section: Introductionmentioning
confidence: 84%
“…Poly(epichlorohydrin‐co‐ethylene oxide) and nano clay, Closite 30B delayed fusion and decreased fusion factor, however, fusion behavior can be tweaked by choosing optimum rotor speed. [ 14 ] Other factors affecting fusion includes temperature and lubricants in formulations. Increased temperature and decreased lubricant level increased probability of fusion.…”
Section: Introductionmentioning
confidence: 99%